Risk Factors for Locoregional Recurrence and Distant Metastasis Following Modified Radical Mastectomy for Localized Breast Cancer in a Nigerian Teaching Hospital - Olaogun, Julius G; Agodirin, Olayide S; Dada, Samuel A; Akanbi, Olusola (Asian Pacific Journal of Cancer Care, 2024)
Background: Mastectomy plays a crucial role in the management of breast cancer, particularly in resource-limited healthcare settings. This retrospective study aimed to evaluate the incidence of locoregional recurrence (LRR) and distant metastasis (DM) after modified radical mastectomy (MRM) for breast cancer, as well as identify associated risk factors. Methods: The study included patients who underwent mastectomy between October 2012 and September 2017. Data analysis was performed using SPSS version 23.0, and the results were presented using descriptive statistics. Inferential statistics were conducted using the chi-square test, with statistical significance set at p < 0.05. Results: Out of 71 patients who underwent MRM during the study period, 63 (88.7%) were eligible for analysis. The age range of the eligible patients was 24-80 years, with a median age of 49 years (IQR, 43-59 years). The size of the breast lump ranged from 2-18 cm (mean, 7.8 ± 3.5 cm), and the duration of the lump varied from 1-48 months (median 6.0, IQR, 4.0-10.0 months). Sixteen (25.4%) patients developed LRR, with a median interval of 9 months (IQR, 6.0-20.0) after mastectomy. Eighteen (28.6%) patients experienced distant metastasis, occurring 9-60 months after surgery (median 19, IQR 12.0-37.0). Fifty percent of patients with LRR also developed metastasis, predominantly affecting the lungs and pleura (55.6%). Risk factors significantly associated with LRR included mean tumor size ≥10cm (p < 0.000), mean lump duration >11 months, advanced disease stage T3/4 (p=0.01), and a higher number of positive lymph nodes (p=0.011). Tumor size (p=0.01) and positive lymph nodes (p=0.015) were identified as predictors of LRR. Conclusion: LRR and distant metastasis are common occurrences following mastectomy. Early presentation of breast cancer and the availability of adequate adjuvant therapies can help reduce the incidence of these complications.